3D modelling of coupled electromagnetic-mechanical responses in REBCO coils involving tape inhomogeneity. (1st May 2022) - Niu, Mengdie; Yong, Huadong; Zhou, Youhe
Abstract: Electromagnetic and mechanical properties are crucial components of high-temperature superconducting magnet in high-field applications. In this research, in order to predict the multi-field behaviors of REBCO coils during the ramping process, the coupled electromagnetic-mechanical model is constructed with consideration of the strain and magnetic field dependences of the critical current of coated conductors (CCs). The 3D modelling is used to characterize the longitudinal in-homogenous critical current of a CC, which also allows for handling the coil with local defects. To verify the reliability of the coupled model, a comparison of numerical simulations with experiments for a small REBCO coil is first performed with special attention on the hoop strain evolution during the magnetization process. On this basis, the coupled model is then utilized to study the influences of local critical current non-uniformity defined by a Gaussian statistical distribution. The numerical analysis shows that, the tape inhomogeneity has an obvious impaction on decreasing the critical current of REBCO coil. And in high-field scenario, the calculated critical current of coil is highly reduced when the mutual interaction between electromagnetic and mechanical fields is considered. Afterwards, a detailed comparative study is carried out in studying the screening current effects of REBCO coil with and without taking the tape inhomogeneity into account. Finally, the effects of cooling-down process, co-winding materials and local defects are investigated to understand their role in electromagnetic-mechanical response of high-field REBCO coils.